PENGARUH ETIKA KERJA ISLAM, MOTIVASI INTRINSIK DAN BUDAYA SEKOLAH ISLAMI DALAM MENINGKATKAN KINERJA SDM - Eko Sumarno (Jurnal Riset Bisnis Indonesia, 2014)
This study aims to describe and analyze the relationship of Islamic Work Ethics, Intrinsic Motivationand Cultural Islamic School on human performance and to develop models of human performanceimprovement based Islamic work ethic, Intrinsic Motivation and Islamic School Culture in SMA IslamSultan Agung Semarang. The population in this study is high school teachers in Islam SMA IslamSultan Agung Semarang which sample is 84 teachers. The data analysis uses Partial Least Square(PLS). These results indicate that: 1) the work ethic of Islam has significant positive effect on theculture of Islamic schools 2) Intrinsic motivation has significant positive effect on the culture of Islamicschools. 3) Islamic work ethic has significant positive effect on performance. 4) Intrinsic motivationhas significant positive effect on performance. 5) Cultural Islamic school has significant positiveeffect on performance.Keywords: Islamic work ethic, intrinsic motivation, Culture Islamic schools and Performance.